1990
DOI: 10.1007/bf00154206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium dobesilate on the blood-retinal barrier in early diabetic retinopathy

Abstract: The effect of calcium dobesilate on the alteration of the blood-retinal barrier was studied in 41 adult-onset, non-insulin dependent diabetic patients with minimal or no retinopathy, randomly assigned to receive either oral calcium dobesilate (1000 mg twice daily) or a placebo for 12 months. The posterior vitreous value and the penetration ratio, determined by vitreous fluorophotometry, reflected stabilisation of blood-retinal barrier permeability in the calcium dobesilate patients and deterioration of blood r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…There have been two randomized placebo-controlled trials demonstrating its efficacy on the progression of early DR. 33,34 However, in another study conducted in 635 type 2 diabetic patients with mild-to-moderate NPDR presenting at the first visit with microalbuminuria, CaD failed in reducing the risk of the development of clinically significant diabetic macular edema (CSME). 35 A recent meta-analysis review has shown that CaD is significantly associated with improving retinal microaneurysms, hemorrhages, exudates, as well as a reduction in whole blood and plasma viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two randomized placebo-controlled trials demonstrating its efficacy on the progression of early DR. 33,34 However, in another study conducted in 635 type 2 diabetic patients with mild-to-moderate NPDR presenting at the first visit with microalbuminuria, CaD failed in reducing the risk of the development of clinically significant diabetic macular edema (CSME). 35 A recent meta-analysis review has shown that CaD is significantly associated with improving retinal microaneurysms, hemorrhages, exudates, as well as a reduction in whole blood and plasma viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…The 1990s saw introduction of medications improving mechanical resistance of capillary walls and decreasing their permeability, such as calcium dobesilate or vinpocetine, yet in the subsequent years their biological impact on DR was not confirmed [36]. Drugs which failed to produce the expected effects included also: aldose reductase inhibitors, acetylsalicylic acid, sulodexide, ticlopidine, antioxidants (vitamin C, E) and rutin derivatives [37][38][39][40].…”
Section: Treatment Of Diabetic Retinopathymentioning
confidence: 99%
“…Calcium dobesilate monohydrate is indicated and approved for the treatment of DR in several countries, with 2 randomized placebo-controlled trials demonstrating its efficacy on the progression of early DR [68,69]. However, it has not been widely used in clinical practice and further research is still needed to elucidate its pleiotropic mechanism of action.…”
Section: Calcium Dobesilatementioning
confidence: 99%
“…The effect of CaD on the progression of early DR is shown in two randomized placebo-controlled studies [68,69].…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation